Analysis of the natural movement of the population under the spectrum of the health crisis - Constantin ANGHELACHE; Mădălina-Gabriela ANGHEL; Ștefan Virgil IACOB (Theoretical and Applied Economics, 2020)

(untitled)
The natural movement of the population refers in principle to births, deaths, divorces and marriages. The reduction in the number of births or the maintenance at a lower level was carried out under the rule of the pandemic crisis, when the couples were reserved in trying to have an increased number of offspring. In the same vein, the reduction in the number of births is due to the fact that the birth rate is influenced by human fertility, a context in which it has been declining and probably under the effect of the health and economic and financial crisis, which has been associated and continues at a fast pace, will impose such a situation. Mortality was also maintained in reasonable terms despite the fact that there were a number of effects of the pandemic crisis, the total number decreased. A structure of deaths by age groups shows that the most affected were those in the groups over 60-70 and even 80 years.